Methodology of project management to improve the execution of infrastructure projects by direct administration of local governments in Jorge Basadre province of the Tacna Region 2018 - Villanueva Vargas, Jean Carlo (2019)
Validation of the Management Methodology to improve the execution of Infrastructure projects by Direct Administration of Local Governments in the Jorge Basadre de la Tacna Province. The type of research is applied because it is oriented towards the validation of an international standard methodology of international prestige and to seek an improvement in the execution of infrastructure projects under the infrastructure modality in the Jorge Basadre Province of the Department of Tacna. It is concluded with a level of confidence of 95%, that the level of validity that the development of a Management Methodology improves the efficiency in the execution of infrastructure projects by direct administration of the Local Governments in the Province Jorge Basadre of the Tacna, regarding the Scope, cost and time, proposed, is high, therefore, it constitutes a viable alternative for the solution of the research problem. The design of the Management Methodology was validated to improve the execution of Infrastructure projects by Direct Administration of Local Governments in the Jorge Basadre de la Tacna Province, based on seven processes appropriate to Public Management.